The effect of education and smoke-free home activity contract on changes in husbands' smoking intensity in the home in North Lombok District, West Nusa Tenggara - Noviar, Ainun Hanin; Prabandari, Yayi Suryo; Padmawati, Retna Siwi (Universitas Gadjah Mada, 2022)
Purpose: Home is the place most at risk of exposure to cigarette smoke. Indonesia recorded that 85% of households are exposed to cigarette smoke. Smoke-free homes (SFH) were initially introduced by the Environmental Protection Agency, United States, 2001 to increase awareness of the health hazards of second-hand smoke (SHS) and one's ability to limit cigarette consumption in the home. The success and effectiveness of implementing smoke-free homes (SFH) cannot be separated from the modification of the behavior of each individual. This study aims to determine the effect of education and smoking-free house activity contracts on reducing the smoking intensity of husbands in the house in North Lombok Regency, West Nusa Tenggara. Methods: This study is a retrospective, pre-, and post-intervention cohort study using secondary data from the Peer Health SHS-LBW Intervention Study in North Lombok Regency, West Nusa Tenggara Province. The data used were baseline data and 6-month data on 733 active smoking husbands who lived in the same house with pregnant women aged less than 4 months when they were respondents in the study. The data will be tested using Chi-square and logistic regression to determine the most influencing variables. Results: The results of the chi-square analysis showed that most husbands with total income did not know/low income 66.67% did not experience changes or tended to increase the intensity of smoking in the house. In the comparative analysis, the value of p = 0.01 was obtained, which means a statistically significant relationship exists between the amount of income and the change in the smoking intensity of the husband in the house. Age, type of work, level of education, location of residence, and the respondent's willingness to attend education and smoke-free house activity contracts did not show a statistically significant relationship with changes in the husband's smoking intensity in the house (p-value>0.05). Conclusion: Education and smoke-free house activity contracts (SFH) did not affect the reduction in the intensity of husbands' smoking in the house.